Identification and Characterization of Volatile Compounds in Antidesma bunius (Buni) Fruit Kombucha During Fermentation - Wulansari, Nadya Treesna; Dharmapatni, Ni Wayan Kesari; Damayanti, Ida Ayu Manik; Raningsih, Ni Made (Sciences of Phytochemistry, 2026)
Buni fruit (Antidesma bunius) is a fruit commonly found in tropical countries such as Indonesia. This fruit has the potential to be developed into kombucha tea because it contains beneficial bioactive compounds. However, the use of buni fruit as kombucha tea remains very limited and has not been studied in depth. The objective of this study was to identify and characterize the volatile compounds in buni fruit kombucha using GC-MS. This study employed a descriptive experimental design to analyze the volatile compounds in buni fruit kombucha after 8 days of fermentation using GC-MS. Buni fruit kombucha fermented for 8 days produced a dark purple color. Based on the analysis of volatile compounds, buni fruit kombucha was identified as containing 30 volatile compounds. The dominant compounds were hexadecanoic acid methyl ester, hexadecanoic acid ethyl ester, 9-octadecenoic acid methyl ester, (E)-9-octadecenoic acid ethyl ester, octadecanoic acid ethyl ester, eicosanoic acid ester, and docosahexaenoic acid methyl ester, which are classified as fatty acid esters and lipids. Additionally, the identified alcohol compounds are patchouli alcohol and 13-tetradecen-11-yn-1-ol. Buni fruit kombucha tea undergoes chemical transformations characterized by the formation of volatile compounds such as esters, alcohols, and fatty acid derivatives as a result of microbial metabolic activity. The profile of the resulting compounds highlights the important role of biotransformation during fermentation in shaping the sensory characteristics and bioactive potential of kombucha tea.